The role of labor in African nation-building - Beling, Willard A.; University of Southern California (New York: Praeger, 1968)
This book examines African labor's role within the post-independence period or, as political scientists are wont to term it, the nation-building period.
"Proceedings of the Institute of World Affairs, volume XLI."
"With one exception ... derived from papers presented at the conference on the role of labor in nation-building which the Institute of World Affairs, under the sponsorship of the University of California, convened December 5-7, 1965, in Idyllwild, California."
Bibliographical footnotes.
rpm 14/03/2018
Loans
Keywords: Labor unions; Labor unions - nation building; Nationalism